Overload level in informal caregivers of children with cerebral palsy - Castro, Ketlin Jaquelline Santana de (2022)
OBJECTIVE: To identify the physical, emotional and social burden of informal caregivers of children with Cerebral Palsy (CP) treated at the outpatient clinic of the Faculty of Physiotherapy and Occupational Therapy (FFTO) of the Federal University of Pará (UFPA).METHODS: This is a descriptive and cross-sectional study with caregivers of children with a clinical diagnosis of CP attended at the FFTO-UFPA physiotherapy sector. The Informal Caregiver Burden Assessment Questionnaire (QASCI) and a form with identification and sociodemographic data of the caregivers were used. The collected data were transcribed to a database in the Excel® program. In order to describe the findings, descriptive statistics (mean, standard deviation, percentage) was used.RESULTS: The sample consisted of six mothers with a mean age of 30.6 + 4.6 years. The subcategory “Implications in personal life” (40.9%), “Family support” (29.1%) and “Financial burden” (29%) were the categories that obtained the highest score in the QASCI questionnaire among the participating caregivers, being classified as moderate.CONCLUSIONS: The increased burden on caregivers was identified in subcategories related to greater physical strain on the caregiver, the lack of a family support network and the increased financial impact on family income. These factors can compromise the caregiver's participation in social activities that are not directly related to the child's care. Emotional factors in this study were not related to the increased burden on caregivers.